IMPROVING STUDENTS’ COMPREHENSION OF POEMS USING TWO STAY-TWO STRAY STRATEGY - Hamiddin, Hamiddin (Jurnal Vidya Karya, 2012)
The study is directed to improve students’ comprehension of poems using the Two Stay-Two Stray strategy. The subject of this study is 23 students of the sixth semester of English department of FKIP at Islamic University of Malang. This study uses collaborative action research design which consists of four main steps: planning, implementing, observing, and reflecting. The data is taken from quiz, observation checklist and field notes. The findings indicate that using TS-TS strategy can improve the students’ comprehension of poems. The average score of students’ test in Cycle 2 is 80 and the students’ active involvement in Cycle 2 is 86%. The data are obtained from the plementation of TS-TS strategy in improving students’ comprehension of poems